Female Same-Sex Bidirectional Intimate Partner Violence in China - Lin, Kai (Journal of interpersonal violence, 2022)
Although there exists a growing body of research on female same-sex intimate partner violence (FSSIPV) as well as bidirectional intimate partner violence (BIPV) among lesbian women, much of this literature focuses on the IPV experience of women living in Western societies such as the United States. The current study represents the very first to explore BIPV among lesbian women in China. In this study, we analyze a survey sample of 225 self-identified lesbian women in China to examine FSSBIPV patterns, pattern-specific rates, and risk factors of FSSBIPV. Using the Latent Class Analysis technique, we discover three main patterns of partner abuse, including bidirectional psychological violence (60%), bidirectional violence multiple types with physical abuse (79.1%), and minimal violence (20.9%). Logistic regressions show that there is no significant demographic, socioeconomic, or attitudinal difference between the bidirectional psychological violence group and the minimal violence group while being younger, cohabitating, and holding pro-IPV attitudes significantly predicted higher odds of experiencing multiple types of bidirectional violence. Contributions to the literature, as well as policy implications, are also discussed.